Radial artery pseudoaneurysm after a glass cut injury: A rare case report - Kaur, Savleen; Sood, Aditya; Luther, Anil (Indian Journal of Case Reports, 2026)
Pseudoaneurysm of the radial artery secondary to direct penetrating trauma, rather than iatrogenic arterial injury, is rare, with reported incidence figures of 0.048–0.05% for pseudoaneurysm following arterial cannulation; the true incidence of post-traumatic cases remains unknown due to sparse reporting. We report the case of a 22-year-old male who presented with a slowly enlarging, pulsatile swelling over the right lateral aspect of the distal forearm, 1 month after an accidental glass-cut injury sutured at a local clinic. Duplex ultrasonography confirmed a 1.5 × 0.6 cm pseudoaneurysm of the distal right radial artery. He underwent surgical exploration with resection of the pseudoaneurysm and end-toend arterial reconstruction, confirmed histopathologically. The post-operative course was uneventful, with good distal perfusion at 3 months of follow-up. This case highlights the need for a high index of suspicion for pseudoaneurysm after any forearm laceration presenting with delayed swelling, and supports early surgical repair as the treatment of choice